Behavioral Counseling Effectiveness Behavior Contract Technique to Decrease Behavior Academic Procrastination of Students - Purnama, Andre Septian; Mursidi, Agus; Trisnawati, Kartini Ayu (International Journal for Educational and Vocational Studies, 2019)
In this study aims to: (1) determine the effectiveness of behavioral counseling behavior contract techniques in reducing the academic procrastination behavior of class XII IPS MAN 2 Banyuwangi students; (2) find out the differences between students of class XII IPS MAN 2 Banyuwangi between the experimental group and the control group that did not receive treatment. The design used is non-equivalent pretest-posttest control group. The sample of this study was 20 students of class XII IPS MAN 2 Banyuwangi which were divided into 2 groups. Academic procrastination behavior was measured using an academic procrastination behavior questionnaire. The data that has been obtained is then analyzed using descriptive analysis. The results showed that: (a) first, the tcount at the output showed the number 27,976 this meant a decrease. If t arithmetic> T table, then H0 is rejected. Which means 27,976> 1,833, thus because H0 is rejected, Ha is accepted, where Ha reads "Behavior Counseling Behavior Contract technique is effective against decreasing academic procrastination behavior of students of class XII IPS MAN 2 Banyuwangi," (b) The results of both studies indicate t-KE ≠ tcount KK (31,771 ≠ 10,801). Therefore, because H0 was rejected, Ha was accepted, where Ha reads "There is a difference in effectiveness between the experimental group that received treatment and the control group that did not receive treatment in reducing the behavior of students' academic procrastination". So it can be concluded that between the experimental group with the control group there are very differences. The final results of this study indicate that the Behavior Counseling Behavior Contract technique can reduce and prevent students' academic procrastination behavior with an increase of 27%.